2020
DOI: 10.1177/2167702620949174
|View full text |Cite
|
Sign up to set email alerts
|

Ruminative Inertia and Its Association With Current Severity and Lifetime Course of Depression

Abstract: Rumination has been consistently shown to play a critical role in the severity and course of depression. Relatively understudied, however, is the nature of rumination across time and how individual differences in the temporal dynamics of rumination may be related to depression. In this study, we investigated the association between ruminative inertia (the degree to which rumination levels are resistant to change from day to day) and both current and past depression in a clinical sample. Participants ( N = 71) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Indeed, previous ESM studies have suggested that worry becomes more strongly associated with positive affect and NA as a sudden shift in depressive symptoms (or the moment of relapse) approaches (van de Leemput et al, 2014;Wichers, 2014;Wichers et al, 2019). Another study on patients with a history of unipolar depression showed that ruminative inertia is positively associated with current levels of depressive symptoms and is negatively associated with the number of past depressive episodes (Bean et al, 2020). However, a direct replication on a clinical sample would still be warranted to establish the clinical relevance of our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, previous ESM studies have suggested that worry becomes more strongly associated with positive affect and NA as a sudden shift in depressive symptoms (or the moment of relapse) approaches (van de Leemput et al, 2014;Wichers, 2014;Wichers et al, 2019). Another study on patients with a history of unipolar depression showed that ruminative inertia is positively associated with current levels of depressive symptoms and is negatively associated with the number of past depressive episodes (Bean et al, 2020). However, a direct replication on a clinical sample would still be warranted to establish the clinical relevance of our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Individual networks showed temporal associations that might be useful for clinical interpretation and use in self-monitoring contexts. A positive autoregressive effect of rumination, which was present for some estimation points for participants 2, 6 and 11, is sometimes termed ruminative inertia (Bean et al, 2020). Becoming stuck in rumination might be a relevant cognitive mechanism that explains negative influences of rumination on depression (Bean et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this is not in line with the original definition of rumination by Nolen-Hoeksema 9 , which assumed ruminative processes to pose more of a trait rather than a reactive state condition 4 . Supporting this assumption of a trait as well as a state pattern of rumination, relatively unstable processes fulfilling the criteria of rumination were found 26 28 . Robinson and Alloy 25 postulated the Theory of Stress-Reactive Rumination, defining rumination as a state.…”
Section: Introductionmentioning
confidence: 56%